PENGARUH ATURAN ETIKA TERHADAP KUALITAS AUDIT YANG DIMEDIASI OLEH PENGENDALIAN MUTU (SURVEI PADA AUDITOR BPK RI) - Korompis, Claudia Wanda Melati (Universitas Sam Ratulangi, 2018)
The fraud cases involving government auditors certainly erode public trust. The importance of improving audit quality to increase the public trust makes author interested in conducting research that seeks to measure the determinants of audit quality. Before Enron and Worldcom’s accounting scandal on 2001-2002, studies that measured audit quality generally still use KAP-size proxies. DeAngelo's (1981: 186), states that: